(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Drug-induced liver injury (DILI) is a significant cause of acute liver disease and one of the leading reasons for the withdrawal of approved drugs from the market. It occurs when medications, herbal products, or dietary supplements cause structural or functional damage to the liver. DILI can range from mild, asymptomatic elevations in liver enzymes to severe liver failure requiring transplantation. The incidence of DILI has increased due to the widespread use of prescription drugs, over-the-counter medications, and herbal remedies, making it an important public health concern. DILI is broadly classified into intrinsic (predictable, dose-dependent) and idiosyncratic (unpredictable, dose-independent) types. Common causative agents include acetaminophen (paracetamol), anti-tubercular drugs, antibiotics, non-steroidal anti-inflammatory drugs (NSAIDs), antiepileptic drugs, anticancer agents, and various herbal supplements. The underlying mechanisms involve oxidative stress, mitochondrial dysfunction, immune-mediated hepatotoxicity, disruption of bile acid transport, and the formation of reactive metabolites that trigger hepatocellular injury. Clinical manifestations include fatigue, nausea, jaundice, abdominal pain, dark urine, elevated liver enzymes, and, in severe cases, acute liver failure. Diagnosis of DILI requires a detailed medication history, exclusion of other causes of liver disease, liver function tests, imaging studies, and causality assessment tools such as the Roussel Uclaf Causality Assessment Method (RUCAM). Early recognition and immediate discontinuation of the offending drug remain the cornerstone of management. Supportive care, specific antidotes such as N-acetylcysteine for acetaminophen toxicity, and liver transplantation in selected cases improve patient outcomes.In conclusion, drug-induced liver injury represents a preventable yet potentially life-threatening adverse drug reaction. Rational prescribing, regular monitoring of liver function during high-risk therapies, pharmacovigilance, patient education, and the development of safer therapeutic agents are essential to minimize the burden of DILI. Continued research into predictive biomarkers and personalized medicine approaches is expected to enhance early diagnosis and prevention, thereby improving patient safety and therapeutic outcomes.